Online Social Movement: Adopsi Teknologi Informasi dalam Melakukan Gerakan Sosial di Indonesia - Ahmad Ismail; Hardiyanti Munsi; Amril Hans (ETNOSIA : Jurnal Etnografi Indonesia, 2019)
This article aims to explain whether the social movements carried out on the internet are limitedto click activism or merely mere symbolic resistance, or even beyond that? The case of the social movement raised in this study is the Akademi Berbagi Movement based on the internet, especially social media. the movement that combines online and offline gives its own nuances in doing social movements. This study used a qualitative approach with the method of connected ethnography carried out for 5 months. From the results of the research, the Akademi Berbagi Movement is one of the forms of the birth of civil society. The movement that combines online and offline has provided the context, validation and attachment of more participation by volunteers in carrying out social movements, thus giving birth to what is called 'online social movements'. This also complements the concept that Nugroho (2011) refers to as "click activism", with the case of the movement raised in this study, social movements carried out on the internet exceed what is called click activism, and volunterism is done more than just being involved in movement online, but volunterism is also done in an offline context so that this movement is not just "click" but also provides real space for movement.